Paleostress analysis from brittle failure and minor structures in Dokan Area, Kurdistan Region, NE of Iraq . - Al-Hakari, Salim H. Sulaiman (Sulaimani Journal for Pure and Applied Sciences, 2016)
The study area is located within the high folded of the northwestern segment of the Zagros Foreland Fold Thrust Belt in northeast of Iraq. Joints, mesofaults, veins and stylolites were studied through seven stations in the Kosrat Anticline. The trend of the fold and the strike of the strata are of NW-SE direction in accordance with the main trend of Zagros folds. New geological map and cross section of the study area were constructed. The exposed rocks of the studied area range in age from Cretaceous up to the Eocene included the following formations (Qamchuqa, Kometan, Shiranish, Tanjero, Kolosh and Sinjar) Kometan and Tanjero formations was taken in consideration for brittle failure analysis . The analyzed structural field data indicate that the investigated area was subjected throughout its geological history to four stress phases. First is primary compressive tectonic phase in the directions N-S, NE-SW and successive phase in the direction ENE-WSW. The second compressive tectonic stress in the direction NW-SE considered as a secondary phase. Third was extension tectonic phase in the direction NE-SW which developed during the final uplift stage of folding is normal to the major folds trend. The fourth is NW-SE extension face considerate as extension stress related to the primary NE-SW compressive stress.
Keywords: analysis; Microtectonic analysis,Brittle fraileranalysis